O presidente desidratado: uma análise da dinâmica da relação executivo-legislativo no Brasil - Brito, Thais Carneiro de (2023)
The dissertation analyzes the theme of coalition presidentialism and the use of Provisional Measures in the Brazilian political context, addressing the impact of Constitutional Amendment nº 32/2001. Coalition presidentialism is a political system in which the President forms coalitions with different political parties to obtain support in the National Congress and improve the stability and effectiveness of the government. One of the tools frequently used by the Executive Branch to maintain political support and advance its agenda is the use of Provisional Measures, which in turn are presidential decrees with the force of law and which can be issued in situations of urgency and relevance, allowing the President to promote changes in legislation without the need for immediate approval from the Legislature. The dissertation investigates the impacts of Provisional Measures on Brazilian democracy, including their implications for the separation of powers and the role of Congress in policy formulation. Methodologically, a comparative analysis was carried out, the strategy of which was based on a survey of the literature on coalition presidentialism, addressing interpretations by authors with significant repercussions in Political Science, such as Schumpeter (2017), Abranches (1988), Dahl (2015), Figueiredo and Limongi (2001, 2003), Octavio Amorim Neto (2016), among others. The results of the dissertation highlight the complexity of the relations between the Executive and the Legislative in Brazilian coalition presidentialism. They also point to democratic challenges, such as the concentration of power in the hands of the President and the impact of party fragmentation on the stability of coalitions and government decision-making.